The presentation of self in the Zoom age: insights from pragmatics and cognitive science - Jean-Rémi Lapaire (Anglophonia)
In the space of just a few weeks, the COVID-19 pandemic imposed alternative frames and new viewing angles upon all members of the academic community. Private homes went public; interactional frames and scripts were subtly altered; displaying or concealing one’s true self became much trickier. Some managed the transition well but many struggled to adjust their public image and social behaviour to the changed circumstances. Video-interviews are now commonplace but the challenges remain. The claim made in this paper is that those interactants who perform nicely and successfully are those who get both their own and other people’s “stories” right, thus avoiding miscommunication and subtle forms of alienation.